Practical considerations in development of a parallel SKYHI general circulation model - Jones, Philip W.; Kerr, Christopher L.; Hemler, Richard S. (Parallel computing, 1995)
We have developed a parallel version of the SKYHI atmospheric general circulation model. The new parallel model has been designed for shared and distributed memory machines that support data parallel, message passing or worksharing programming paradigms. The newly developed model has a framework that makes the code easier to understand, maintain, and modify, increasing the model's flexibility and scientific productivity. Numerous model changes are described (code design, programming models, language choice, data decomposition, communications, table lookups, memory management, and i/o) that were necessary to develop the model. The performance and verification of the model is described on several systems including a shared-memory machine with high-level worksharing and a distributed-memory system with a data parallel programming paradigm.